Factors influencing subjective well-being in individuals with functional dyspepsia — a path analysis of sex and psychological factors - Volarić, Mile; Babić, Emil; Kurevija, Tomislav; Babič, František; Volarić, Nikola; Majnarić, Ljiljana Trtica (Frontiers in Medicine, 2026)
BackgroundFunctional dyspepsia (FD) is a common gastrointestinal (GI) disorder which significantly impacts quality of life and subjective well-being (SWB). Psychosocial factors have been linked to FD symptoms, which places this disorder among the “disorders of gut-brain interaction.” Recent studies suggest notable sex differences in symptom expression and the level of disruption of daily activities. This study aims to explore the impact of sex on associations between psychological factors and SWB in individuals with FD.MethodsThe study included 191 adults referred to their first endoscopic examination of the upper GI tract due to dyspeptic symptoms. Patients completed validated measures assessing GI symptoms, GI and extra-GI comorbidities, health-related habits, psychological traits (somatization, stress resilience), and indicators of SWB (life satisfaction, positive and negative experiences). Multiple regression and hierarchical block regression analyses were conducted to identify predictors of SWB and to examine the potential moderating role of sex and psychological factors. Subsequently, path analysis was conducted to explore potential causal pathways among sex, psychological variables and SWB.ResultsParticipants displayed relatively homogeneous characteristics according to sex. Two main subgroups were identified: a larger group of highly educated, working-age individuals and a smaller group of older adults (>60 years) with higher comorbidity levels. Psychological factors, stress resilience and somatization emerged as the strongest predictors of SWB, while health and lifestyle factors had modest effects. Sex was identified as a significant determinant of SWB in the complex hierarchical model, but only after controlling for somatization and stress-resilience. The path model indicated that other sex-related factors may also influence SWB.ConclusionResults pointed toward the need to involve psychological constructs like somatization and stress resilience in studies examining SWB in individuals with FD. The importance was highlighted of examining the gender-related (socially conditioned) factors associated with SWB, and the need to separately assess these factors in older and younger individuals with FD (<60, ≥60). The study revealed a complex interactive network between age, gender, and SWB-related factors, supporting the biopsychosocial model of FD. However, identifying a suitable methodological framework to elucidate these complex relationships remains a challenge.